Enhancing Staff Induction Training on Performance of Public Universities in Coastal Region, Kenya - Kombich, Maureen Chepkemoi; Nyaboga, Ibrahim Maticha (International Journal of Research in Interdisciplinary Studies, 2024)
The goal of this research was to investigate how staff induction training impacts the performance of non-teaching employees at Public Universities in the Coastal Region. The selected Universities for this research were the Main Public Universities namely Pwani University, Technical University of Mombasa, and Taita Taveta University. These universities were choses as focal points due to the absence of prior research in this area and the identification of pertinent issues within the region. The objectives focused on inclusivity of employee understanding of the University’s vision and mission, procedures and policies, technical and practical skills, and job requirements and clarity as components in the staff induction were results to better performance. The evaluation employed the theoretical frameworks of Employee Induction theory (TPI), Organizational role theory, and Kirkpatrick Four-level Model. A descriptive research design was adapted, and data collection involved both primary and secondary sources. Stratified sampling was used to capture employee groups from each university, with a total target population of 728 non-teaching staff members. However, 124 respondents were ultimately included in the study. Data collection methods included structured questionnaires and interviews, with qualitative data analysed thematically and quantitative data assessed using descriptive statistical methods in SPSS version 28. The method of probability used were stratified sampling to ensure comparability and precision. Data collection involved structured questionnaires and interviews, allowing for a comprehensive understanding of participants' perspectives. Pre-testing and refinement of data collection instruments ensured validity and reliability, with a content validity index of 0.894 and a Cronbach's Alpha value of 0.9, respectively. The qualitative data was subjected to thematic analysis in order to identify significant themes, and the quantitative data was assessed using descriptive statistical methods in the Statistical Package for the Social Sciences (SPSS) version 28. The findings revealed significant response rate from both questionnaire recipients (84.9%) and interviewees (50%), highlighting the relevance of the study's objectives. Analysis of demographic data uncovered insights into staff demographics, tenure, and job perceptions, emphasizing the importance of effective induction programs in promoting job satisfaction and organizational commitment. The results identified aspects of staff induction that significantly boost university performance. It shows how effectively communicating the university's vision and mission, streamlining policies and procedures, enhancing induction training, ensuring clarity in job descriptions fostering a supportive environment, providing necessary tools and equipment, and improving policy training and implementation. Challenges identified included gaps in policy comprehension, ineffective communication of university goals, and inadequate training on workplace systems and procedures. Recommendations focus on enhancing induction programs to integrate organizational vision, clarify roles and responsibilities, and provide practical skills for job performance. Recommendations focus on enhancing induction programs to integrate organizational vision, clarify roles and responsibilities, and provide practical skills for job performance within Public Universities in the Coastal Region of Kenya and beyond.